Interfacial and durability aspects of extrinsic Fabry-Perot interferometric sensors in carbon fibre composites - Etches, J A (Cranfield University, 2003)
This thesis is concerned with the interfacial and durability aspects of Extrinsic Fabry- Perot Interferometric (EFPI) sensors embedded in carbon fibre reinforced composites. Fibre optic sensors are being used in many long term applications and, as is the case for all sensor types, the ability of the EFPI sensors to monitor accurately the measurands of interest over the lifetime of the structure must be proved. Therefore, the aim of this work was to examine the interface between the EFPI sensors and the structures, and then to evaluate the durability of that interface and the sensors. The first stage was an examination of the EFPI sensors including the method of manufacture, interrogation option and inherent strength of the sensors. It was found that the sensors have a very low tensile load to failure (~0.5 N). This was improved by using a resin reinforcement, which was applied to the capillary ends. However, this had implications for the overall sensor size and that influenced their embedment suitability. The second stage was interfacial characterisation; this was achieved through the examination of the surface energy of the sensors, carried out by contact angle measurements; and the interfacial shear strength of the sensors to matrix, using a new variation on the single fibre pull-out technique that involved the use of optical fibres and composite prepreg. Overall, it was found that the silane treatment of the fibres increased the surface energy but for the interfacial shear results the data was less conclusive due to the scatter present within the results. The durability of the sensors was examined through their embedment into carbon fibre composite samples and exposure to tension/compression fatigue loading. From initial quasi-static work it was found that the embedment of the sensors had no significant effect on the composite samples. However, the sensors failed at a strain levels of 0.4% in tension and at 1.1% in compression; the compression strain level was at the point of composite failure. Under fatigue loading the sensors could survive a million cycles at R=-1 at a max stress level of 156 MPa and maintain their reliability. If the tensile loading was increased then the sensors would fail within a few thousand cycles. However, if the compressive stress was increased the sensors survived but the reliability was affected. Overall, it was felt that with some improvements to the sensor design they should be able to survive and provided useful data when exposed to axial tension/compression fatigue regimes.
Keywords: EFPI